TSN-based routing and scheduling scheme for Industrial Internet of Things in underground mining. (October 2022) - Zhang, Yinghui; Wu, Jiamin; Liu, Mingli; Tan, Aiping
Abstract: Recently, there has been a growing interest in Time-Sensitive Networking (TSN) research in the Industrial Internet of Things(IIoT). The research on real-time and reliable IIoT transmission technology based on TSN has received extensive attention. Especially in some industrial scenarios, such as the safety monitoring of the underground construction environment, the real-time and reliability of data transmission is very important due to the long tunnel and complex structure in underground mining. It is a huge challenge to ensure that the data collected by the sensor has a slight end-to-end delay to the receiving end. A routing scheduling method is proposed based on TSN for IIoT applications in underground mining. Firstly, according to the characteristics of large-scale and distributed hybrid topology in mines and the delay constraints of TSN, the multi-hop routing cooperative scheduling problem S is defined. It is proved that the problem is NP-Hard. Secondly, two algorithms are proposed for problem S : (1) greedy algorithm based on local shortest delay; (2) heuristic algorithm based on an ant colony. Finally, a comparative experimental analysis of the proposed algorithm is carried out, proving that this paper's algorithm performs better in terms of delay and jitter.